Critical Limb Ischemia and Its Impact on Patient Health Preferences and Quality of Life—An International Study - Pisa, Giovanni; Reinhold, Thomas; Obi-Tabot, Eliot; Bodoria, Maria; Brüggenjürgen, Bernd (International Journal of Angiology, 2012)
Critical limb ischemia (CLI) has a significant impact on patients' quality of life (QoL). Despite cost utility evaluations being required by different authorities, data on patient health preferences and utilities for CLI are scarce. Hence, the objective of this study was to assess the impact of CLI on health preferences and health status of affected patients, and to generate health state utilities. In the International Study, 200 patients with CLI (stages III and IV according to Fontaine scale) were interviewed by trained interviewers with a discrete choice instrument, a standard gamble (SG), and the EuroQol-five dimension (EQ-5D) questionnaires (Marten Meesweg, Rotterdam, Netherland). Conjoint analysis showed that a planned amputation (33%) was the most relevant health attribute followed by ambulatory function (25%) and chronic pain (15%). Non-dependence on caregiver impacted on patient health state preference considerably, whereas healing of ulcer/skin lesions had less impact. Preference values obtained from the SG were 0.84, for an amputation subpopulation arriving at 0.70. The EQ-5D index values as well as the EQ-5D visual analog scale for patients with CLI were 0.56. The QoL data of patients with CLI result in decreased QoL and preference values with a planned amputation.
Keywords: critical limb ischemia; peripheral artery disease; quality of life; utility; discrete choice model